2023
DOI: 10.1101/2023.02.13.23285881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring transmission intensity of trachoma with serology

Abstract: Trachoma, caused by ocular Chlamydia trachomatis infection, is targeted for global elimination as a public health problem by 2030. To provide evidence for use of antibodies to monitor C. trachomatis transmission, we collated IgG responses to Pgp3 antigen, PCR positivity, and clinical observations from 19,811 children aged 1-9 years in 14 populations. We demonstrate that age-seroprevalence curves consistently shift along a gradient of transmission intensity: rising steeply in populations with high levels of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…The consistently low Pgp3 seroprevalence appeared to be more reflective of the low level of infection and TF prevalence observed in these districts and others, suggesting that Pgp3 as a single measure of antibody response may be a reliable indicator [ 21 ]. As more countries collect serological and infection data within their programmatic surveys, the cumulative data may help understand the comparative usefulness of these 2 indicators to trachoma surveillance and may help in the development of actionable programmatic thresholds [ 21 ]. Because of the wait and watch approach, at least 200,000 doses of azithromycin were conserved in these 2 districts in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consistently low Pgp3 seroprevalence appeared to be more reflective of the low level of infection and TF prevalence observed in these districts and others, suggesting that Pgp3 as a single measure of antibody response may be a reliable indicator [ 21 ]. As more countries collect serological and infection data within their programmatic surveys, the cumulative data may help understand the comparative usefulness of these 2 indicators to trachoma surveillance and may help in the development of actionable programmatic thresholds [ 21 ]. Because of the wait and watch approach, at least 200,000 doses of azithromycin were conserved in these 2 districts in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons to explain this finding could be that CT694 may be a longer-lived antibody or that it requires fewer infections for someone to seroconvert to CT694 compared to Pgp3. The consistently low Pgp3 seroprevalence PLOS NEGLECTED TROPICAL DISEASES appeared to be more reflective of the low level of infection and TF prevalence observed in these districts and others, suggesting that Pgp3 as a single measure of antibody response may be a reliable indicator [21]. As more countries collect serological and infection data within their programmatic surveys, the cumulative data may help understand the comparative usefulness of these 2 indicators to trachoma surveillance and may help in the development of actionable programmatic thresholds [21].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Perhaps as a result of unsanitary living arrangements, a lack of clean water, and inadequate toilets that facilitate the spread of illness. It is a public health issue that affects 42 nations and accounts for 1.9 million cases of blindness or visual impairment Tedijanto et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A key summary statistic from the age-seroprevalence curve is the seroconversion rate, which is one measure of chlamydia force of infection [6]. In the absence of seroreversion, IgG seropositivity by age reflects the cumulative incidence of prior exposure to chlamydia infection in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated marked increases in seroprevalence with age in trachoma endemic regions and limited antibody responses in populations near elimination [35]. A key summary statistic from the age-seroprevalence curve is the seroconversion rate, which is one measure of chlamydia force of infection [6]. In the absence of seroreversion, IgG seropositivity by age reflects the cumulative incidence of prior exposure to chlamydia infection in the population.…”
Section: Introductionmentioning
confidence: 99%